The elite and the marginalised: an analysis of public spending on mass education in the Indian States - Sarmistha Pal; Sugata Ghosh (Institute for the Study of Labor (IZA), 2008)
In the context of strikingly low literacy rates among Indian women and low caste population, the paper explores whether and how far the interests of the marginalized poor are undermined by the dominant elite consisting mainly of the landed and the capitalists. We distinguish the dominant elite from the minority elite (i.e., elected women and low caste representatives in the ruling government) and also the marginalised as measured by the state poverty rate. Results based on the Indian state-level data suggest that a higher share of land held by the top 5% of the population lowers public spending on education while presence of capitalist elite, as reflected in greater degree of industrialisation enhances it, even in poorer states; the landed elite thus appears to be unresponsive to the underlying poverty rate. The effect of minority representation in the government appears to have a limited impact, indicating a possibility of their non-accountability to serve their cohorts and/or a possible alliance with the dominant elite.
urn:nbn:de:101:1-2008101456
Keywords: I28; 330; Literacy among women and low caste; dominant landed and capitalist elite; minority elite; poor and the marginalised; education spending; development and non-development spending; India; Bildungschancen; Öffentliche Bildungsausgaben; Teilstaat; Analphabetismus; Soziale Schicht; Elite; Interessenpolitik; Indien